Sexualkriminalität Erscheinungsformen, Sanktionierung, Legalbewährung und kriminelle Karrieren - Gundlach, Timo (Universitätsverlag Göttingen, 2020)
Few crimes capture the interest and attention of the public as sexual driven crime. Relapsing sex offenders especially spark debates on how best to deal with this particular group. Incidents of serious sexual crimes are, fortunately, rare in Germany which partly complicates empirical research into sexual criminality. This study aims to contribute to an understanding of sexual crimes by providing an overview of such offences in Germany by nature of the offence, offender-types, penalties and (partially) criminal careers from the perspective of judicial oversight of sexual crime. The study examines 9,430 sexual offenders from all over Germany based on data from the Federal Central Criminal Register where either custodial sentences were served or non-custodial sanctions imposed in the base year. It tracks the sample group over six years comparing their outcomes with other non-sexual offender types.